Two cases of successful treatment of acute right heart failure with Impella RP®. (29th April 2020) - Santer, David; Boltres, Anita; Koechlin, Luca; Hunziker, Patrick; Jeger, Raban; Maurer, Markus; Grapow, Martin; Eckstein, Friedrich; Reuthebuch, Oliver
Abstract: Post‐operative right coronary artery occlusion is a serious complication that demands acute coronary revascularization to prevent myocardial infarction. We present two cases with acute right coronary artery obstruction caused by (1) transfemoral aortic valve implantation and (2) acute type A aortic dissection. Although coronary artery bypass grafting was performed intraoperatively, right heart failure was observed in both cases. The Impella RP® device offers temporary right ventricular mechanical support; wherefore, we decided to deploy it in both patients. The devices were uneventfully and successfully implanted to bridge for recovery of the right heart. We report the perioperative course of the patients as well as their condition at 1 year follow‐up.